Posterior Layering of Fluorine-18 Fluorodeoxyglucose in the Urinary Bladder - Khoo, Alex Cheen Hoe (Indian J Nucl Med, 2018)
An 89-year-old man undergoing fluorine-18 fluorodeoxyglucose positron emission tomography/ computed tomography ((18)F-FDG PET/CT) study posttherapy for hepatocellular carcinoma was noted to have (18)F-FDG posterior layering of the urinary bladder. This phenomenon of posterior layering of (18)F-FDG in the urinary bladder during PET/CT studies is physiological, and it is important to recognize to avoid misinterpretation and unnecessary investigations. The hypotheses for the cause of this phenomenon are highlighted in these interesting images including the reversed phenomenon where there is anterior layering of (18)F-FDG.